Chemical Constituents and Anticancer Effects of the Essential Oil from Leaves of Xylopia laevigata - Quintans, Jullyana de S. S.; Soares, Bruno M.; Ferraz, Rosana P. C.; Oliveira, Allan C. A.; da Silva, Thanany B.; Menezes, Leociley R. A.; Sampaio, Marília F. C.; Prata, Ana Paula do N.; Moraes, Manoel O.; Pessoa, Claudia; Antoniolli, Angelo R.; Costa, Emmanoel V.; Bezerra, Daniel P. (Planta Medica, 2013)
Xylopia laevigata, popularly known as “meiú” and “pindaíba”, is a medicinal plant used in the folk medicine of the Brazilian Northeast for several purposes. The chemical constituents of the essential oil from leaves of X. laevigata, collected from wild plants growing at three different sites of the remaining Atlantic forest in Sergipe State (Brazilian Northeast), were analyzed by GC/FID and GC/MS. The effect of the essential oil samples was assessed on tumor cells in culture, as well on tumor growth in vivo. All samples of the essential oil were dominated by sesquiterpene constituents. A total of 44 compounds were identified and quantified. Although some small differences were observed in the chemical composition, the presence of γ-muurolene (0.60–17.99 %), δ-cadinene (1.15–13.45 %), germacrene B (3.22–7.31 %), α-copaene (3.33–5.98 %), germacrene D (9.09–60.44 %), bicyclogermacrene (7.00–14.63 %), and (E)-caryophyllene (5.43–7.98 %) were verified as major constituents in all samples of the essential oil. In the in vitro cytotoxic study, the essential oil displayed cytotoxicity to all tumor cell lines tested, with the different samples displaying a similar profile; however, they were not hemolytic or genotoxic. In the in vivo antitumor study, tumor growth inhibition rates were 37.3–42.5 %. The treatment with the essential oil did not significantly affect body weight, macroscopy of the organs, or blood leukocyte counts. In conclusion, the essential oil from the leaves of X. laevigata is chemically characterized by the presence of γ-muurolene, δ-cadinene, germacrene B, α-copaene, germacrene D, bicyclogermacrene, and (E)-caryophyllene as major constituents and possesses significant in vitro and in vivo anticancer potential.
Keywords: Xylopia laevigata; Annonaceae; essential oil; chemical composition; antitumor